Acute haemorrhage from a retroperitoneal liposarcoma: a rare presentation. (8th February 2018) - Al Sheikh, Mohammed; Simson, Nick; Obi-Njoku, Obinna; Qteishat, Ahmed
Abstract : A previously healthy 61-year-old Caucasian woman presented to the emergency department after collapsing at home with associated abdominal pain radiating to her back. An urgent CT angiogram was requested to rule out a ruptured aortic aneurysm. This showed a large 21 cm fat-containing lesion arising from the mid-pole of the left kidney, with an adjacent 4 cm perirenal haematoma. An initial diagnosis of a ruptured angiomyolipoma was made. Her haemoglobin was 105 g/L, with a creatinine of 104 mmol/L and an eGFR of 47 mL/min. Her clotting profile was normal. Following resuscitation, she was taken to the operating room and underwent an emergency open left radical nephrectomy via a left flank incision. Her recovery was uneventful and she was discharged home after 6 days. The histopathology confirmed a well-differentiated liposarcoma.